Analysis of the Urban Millennial Travelers’ Intention - Derinta Entas; Nenny Wahyuni; Murhadi; Edric Maulana (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: This study aims to identify the main factors that influence the travel intention of urban millennial travelers and why travel intentions are essential to be studied by stakeholders. Research methods: This research uses a qualitative descriptive approach, which implications travel intention from the point of view of urban millennial travelers to the main factors that affect travel intention. Travel Intention became a unit of analysis and the main focus of this research. Purposive sampling techniques were used to establish the sample number of this study, which is 100 respondents. Results and discussion: The results showed that the identification of travel intention popular among urban millennial travelers in Jakarta four important factors significantly affect the quality of the place that is the leading destination of urban people in Jakarta. The factors are, self-conformity, attitude, destination image, and perceived quality. Implication: The attitude became a reasonably popular factor that the respondents chose. Keywords: travel intention, millennials urban traveler, TCL model.